A glance at our New Dean - UiTM, Fakulti Sains Gunaan (Faculty of Applied Sciences, 2019)
Professor Dr Farida Zuraina bt Mohd Yusof, a PhD graduate from the University of Ulster, Northern Ireland, was appointed as the new Dean of the Faculty of Applied Sciences (FSG), Universiti Teknologi MARA, effective from 1 January 2019 until 31 December 2021. Her appointment came about from the first voting system conducted at FSG. Prof. Dr Farida Zuraina expressed her gratitude to everyone who voted her and promised to be efficient and trustworthy in carrying out her responsibilities and duties as a dean. After 5 months into the post, she is thriving well and getting full, undivided support from all the faculty members.